St. Stefan of Perm’: A Dialogue between Traditions and the Tradition of Dialogue - Limerov, Pavel (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2010)
Bishop Stefan of Perm’ was a religious figure of considerable importance in medieval Russia, famous for converting a Finno-Ugrian people, the Permians (now known as the Komi) to Christianity. The Permians inhabited lands in north eastern Europe bordering the central and northern Urals, known in the Russian chronicles as Perm’ Vychegodskaia and Greater Perm’. The selfless work of St. Stefan was highly appreciated by his contemporaries; thus in documents dating from the fifteenth and sixteenth centuries he is listed among the most outstanding Russian Orthodox churchmen: figures such as Petr and Aleksii of Moscow, Leontii of Rostov, Sergii of Radonezh, Kirill of the White Lake, and Varlaam of Khutyn [Lytkin 1889: 13]. He was officially canonized in 1547 at Metropolitan Makarii’s Council, one of the first thirty saints to be canonized in Muscovy [Golubinskii 1889: 204]. A few years after St. Stefan’s death in 1396, Epifanii Premudryi, a monk at St. Sergii’s Trinity Monastery, composed his vita [Prokhorov 1995]. To this day this work remains the chief source of historical information about St. Stefan of Perm’.